Formação continuada de gestores da educação: uma perspectiva interdisciplinar - Camargo, Sheila Siqueira (2010)
This paper work proposes the articulation of an interdisciplinary perspective of the Management of public schools in the educational context of the beginning of the XXI century, discussing the ontological, epistemological and praxiological aspects involved in this process, justifying the need of such approach and trying to identify the factors that would facilitate and/or complicate this proposal. The research is, thus, guided by the question: Is it possible to identify ontological, epistemological and praxiological aspects in the continued education of Educational Managers that are able to subsidize its interdisciplinary practice on behalf of a participative democratic management in the direction of a qualified school? . As theoretical parameters for the proposed discussion, there are the legislation in force (Lei de Diretrizes e Bases da Educação e Proposta Curricular do Estado de São Paulo Law of Directives and Educational Bases for Education and Curricular Proposal of the State of Sao Paulo); the Idea of Interdisciplinarity (MATURANA, 1990; MORIN, 2000; MACHADO, 2004; FAZENDA, 2005; LENOIR, 2005; GUSDORF, 2006); curriculum (GIROUX, 1997); Continued Education of Educational Managers (LUCK, 2001; FERREIRA, 2006; BRITO, 2009); and Educational Management (HARGREAVES e FINK , 2007; MARTINS, 2007; PARO, 2007; THURLER, 2007). The research also counts on thesis that report praxiological processes of Managers and constitute part of the material for the theoretical articulation and analysis, along with the testimonials of two Supervisors, five Coordinator Professors of the Pedagogical Workshops and five Managers. As a result of such reflection, there is the possibility of constructing the notion of Continued Education of Educational Managers in an interdisciplinary perspective, with the prospection of the strengths in this process, focused on the ontological, epistemological and praxiological aspects of such practice, what resignifies the notion of Management in the current educational context